Role of cytokinins in seed development in pulses and oilseed crops: Current status and future perspective - Sharma, Sandhya; Kaur, Parampreet; Gaikwad, Kishor (Frontiers in Genetics, 2022)
Cytokinin constitutes a vital group of plant hormones regulating several developmental processes including growth, cell division, and have a strong influence on grain yield. Chemically, they are the derivatives of adenine and are the most complex and diverse group of hormones affecting plant physiology. In this review, we have tried to provide a molecular understanding of the role of cytokinins in developing seeds, with special emphasis on pulses and oilseed crops. Further, the role of cytokinin responsive genes including cytokinin oxidases and dehydrogenases (CKX) have been emphasized upon. Recently, it has been shown that manipulation of these genes by mutation, RNA interference, or genome editing has a significant effect on seed number and/ or weight in several crops. Despite this information on cytokinins, their potential in improving crop quality and yield remains underutilized. This is primarily due to the multigene control of cytokinin expression. Moreover, the cytokinins act synergistically with auxins and gibberellins in accelerating plant growth and development. The information summarized in this review will help the researchers in innovating newer and more efficient ways of manipulating cytokinin expression including CKX genes with the aim to improve crop production, specifically of pulses and oilseed crops.